2010
DOI: 10.1007/s13197-010-0155-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of modified atmospheric packaging on the shelf stability of paneer prepared by adopting hurdle technology

Abstract: Paneer was prepared by application of hurdle technology (HT) and its shelf stability studied by modified atmospheric packaging (MAP). The hurdles adopted comprised of water activity (aw), pH, preservative and MAP. The aw was reduced by using NaCl (1-3%), citric acid (CA, 0.01-0.1%) and potassium sorbate (0.1%). NaCl and CA at 3 and 0.1% reduced aw from 0.994 to 0.970 and pH from 5.6 to 5.1, respectively. Sensory scores of all samples decreased (p ≤ 0.05) from control during storage at different temperatures, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 2 publications
1
16
0
Order By: Relevance
“…However at the end of the storage, T2 had a significantly (p<0.05) lower water activity than other treatments, T3 and control had nonsignificant (p>0.05) differences and T1 sample had significantly (p<0.05) higher water activity than the other treatments (Table 4). Thippeswamy et al, (2011) observed that as the concentration of NaCl increased for dipping paneer from 1-3%, a w decreased from 0.994 to 0.970. The reduction in a w in paneer with several humectants was observed by Singh et al, (1989), Jayaraj and Patil (1999), Singh and Rai (2004) during storage period.…”
Section: Water Activity (A W )mentioning
confidence: 96%
See 1 more Smart Citation
“…However at the end of the storage, T2 had a significantly (p<0.05) lower water activity than other treatments, T3 and control had nonsignificant (p>0.05) differences and T1 sample had significantly (p<0.05) higher water activity than the other treatments (Table 4). Thippeswamy et al, (2011) observed that as the concentration of NaCl increased for dipping paneer from 1-3%, a w decreased from 0.994 to 0.970. The reduction in a w in paneer with several humectants was observed by Singh et al, (1989), Jayaraj and Patil (1999), Singh and Rai (2004) during storage period.…”
Section: Water Activity (A W )mentioning
confidence: 96%
“…The method as described by Buch et al, (2014) was followed for the estimation of FFA. The a w of paneer was measured using a hand-held, portable digital water activity meter (Aqua lab dew point water activity meter 4TE, USA) according to the method of Thippeswamy et al, (2011) with little modification.…”
Section: Physicochemical Analysismentioning
confidence: 99%
“…Several previous studies have reported an increase in the shelf life of traditional dairy foods using hurdle technology, water activity changes, increase in sugar content etc. (Kumar and Srinivasan 1982;Biradar et al 1985;Thakur et al 1992;Kumar et al 1997;Sharma et al 2001), however, not much scientific literature is available on the use of MAP for extending the shelf life of traditional dairy foods except as reported by Biradar et al (1985) for peda, Rai et al (2008) and Thippeswamy et al (2011) for paneer and Londhe et al (2012) for brown peda.…”
Section: Introductionmentioning
confidence: 99%
“…(Kumar and Srinivasan 1982;Biradar et al 1985;Thakur et al 1992;Kumar et al 1997;Sharma et al 2001). However, not much of the scientific literature is available on use of MAP for extending the shelf life of traditional dairy foods except those reported by Londhe et al (2012) for brown peda and Rai et al (2008) and Thippeswamy et al (2011) for paneer.…”
Section: Introductionmentioning
confidence: 99%